Fine Bubble Technology in Aquaculture: A Review of Enhanced Nutrient Uptake - El Java, Achmad Syah Nizar; Haetami, Kiki; Putri, Triwidiyanti Rosmayani; Putra, Agustinus; Rizkia, Syifa Nur; Goenisa, Jihan; Humaira, Najma (Departemen Akuakultur FPIK UNDIP, 2025)
Freshwater aquaculture in Indonesia encounters critical challenges related to production efficiency and environmental sustainability, where feed costs account for 60–70% of operational expenses, and conventional aeration systems achieve only 8–15% oxygen transfer efficiency while inducing excessive turbulence that stresses fish. This study aims to systematically review fine bubble technology applications to improve nutrient absorption efficiency in freshwater aquaculture systems. A comprehensive literature search was performed across ScienceDirect, SpringerLink, PubMed, Google Scholar, and nationally accredited journals from 2013 to 2024 using the keywords “fine bubble,” “microbubble,” “nanobubble,” and “nutrient absorption” with Boolean operators. Selected articles focused on peer-reviewed studies addressing fine bubble implementations and nutrient absorption mechanisms in freshwater aquaculture. The findings reveal that fine bubble technology, comprising microbubbles (10–50 μm) and nanobubbles (<1 μm), demonstrates outstanding performance by achieving 85–95% oxygen transfer efficiency compared to conventional systems (8–15%), maintaining dissolved oxygen levels up to 25.39 mg/L while reducing ammonia by 83.33%. In recirculating aquaculture systems (RAS), this technology significantly enhanced biomass growth, improved feed conversion ratios from 1.8 to 1.4, reduced energy consumption by 30–40% (1.2–2.0 kWh/kg O₂ vs. 2–4 kWh/kg O₂), and ensured uniform oxygen distribution with minimal turbulence stress. Practically, these results suggest that fine bubble technology holds transformative potential for sustainable freshwater aquaculture intensification by optimizing nutrient uptake efficiency, improving water quality, and reducing energy costs. This technology is highly recommended for application in RAS and aquaponic systems, while further research is needed to develop cost-effective solutions for small-scale farmers and integrate IoT-based monitoring systems to support broader commercial scalability.